THE IMPORTANCE OF DETERMINING THE (NON)EXISTENCE OF MARRIAGE WHILE ACQUIRING SHARE IN THE COMPANY - Plamenac, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The main subject of this paper is analysis how digitalization can contribute in resolving legal concerns which were observed in practice and which are related to the fact that a share in the company is the object of common property of spouses. There are shown the main provisions of family law in Republic of Serbia, in order to approach the meaning of common property of spouses, as well as material and procedural provisions related to the company law in Republic of Serbia, regulations on registration of companies, data and documents which are of importance for the companies and which are the object of registration. Goal is to show that checking of fact is natural person who is achieving the share in the company married while undertaking legal actions in order to achieve that share and automatic, electronic recording and centralized exchange of these data between public notaries and other public authorities in that process, in the future, can greater legal security in Republic of Serbia and in the neighborhood states – Croatia and Slovenia.